Disaster Preparedness Psychoeducation for Students of Athirah Islamic School - Umar, Hasdinar; Paotonan, Chairul; Baeda, Achmad Yasir Baeda Yasir; Rahman, Sabaruddin Rahman; Assidiq, Fuad Mahfud; Husain, Firman; Nadjmi, Nurul; Nur, Sitti Hijraini; K, Riswal; Amaliyah, Novriany; Umar, Muh. Fitrah Ramadhan; Munadiah, Nurul; Sakinah, Whina (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Makassar is one of the cities in Indonesia that is unlikely to be free from natural disasters. The problem is that the community, especially school-age children, is not yet responsive and alert and does not understand disaster preparedness's importance. Low knowledge, lack of information provision, and disaster risk management can increase the number of victims. Athirah Islamic School, one of the partners in this service, provides facilities for Psychoeducation activities for students. From this problem, a solution for disaster risk reduction is needed by giving psychoeducation (disaster mental health) and disaster preparedness around general reactions (behavior, emotion, cognition, and physical). Psychoeducation materials will be delivered by the Bosowa University psychology team, also partners in this Service activity. The implementation method of this service program includes mentoring and disaster preparedness training from a psychological perspective. The research method used in this service is experimental with a pretest-posttest design approach. The statistical analysis results showed a difference in student knowledge regarding disaster preparedness before and after participating in psychoeducation with a sig <0.05. This service concludes that the training provided to Athirah Bukit Baruga Islamic Middle School students positively impacts students' disaster preparedness knowledge.